Alvin Ho : allergic to dead bodies, funerals, and other fatal circumstances ; - Look, Lenore (Schwartz & Wade, 2011)
A fearful second grader in Concord, Massachusetts, learns about death when his grandfather's best friend passes away and he offers to accompany his grandfather to the funeral.